A comprehensive optical characterization of linear Fresnel collectors by means of an analytic study. (1st January 2017) - Abbas, R.; Martínez-Val, J.M.
Highlights: Performance of linear collectors is assessed via the impinging energy on the mirrors. Analytic methods are established to design LFCs. Innovative designs are proved to increase efficiency with EW orientation. Energy effectiveness of LFCs and PTCs are compared for different latitudes and tilts. Abstract: Linear Fresnel collectors lead to a reduction of investment costs compared to parabolic trough collectors, but it is not yet certain whether this implies a reduction of levelyzed cost of electricity or not. In order to analyze the optical behavior of concentrators ray trace models are often used. However, such methodology leads to time-consuming codes that make difficult to optimize all design variables. In this work an analytic method is used in order to characterize the effect of the design variables on the annual energy impinging onto the reflecting surface, and results for two different locations are compared. The paper leads to the notable conclusion that the ratio of energy impinging onto the reflecting surface of Fresnel collectors is closer to that of parabolic troughs at low latitude locations.